Application of a metal solubility model to geochemical survey data - Lenham, Jessica Chloe (2005)
In areas where heavy metals are introduced into or onto land where they would not normally be present at elevated concentrations, then that land could be considered to be contaminated. A simple way of determining the magnitude of contamination by heavy metals is to measure the total metal concentration in the soil. However, this simple measure is a poor way of assessing the potential risks to the environment and human health. A more effective risk assessment can be achieved by analysing the proportion of the total metal that exists in a mobile or bioavailable form, in other words, the metal solubility. Unfortunately metal solubility is more difficult and costly to measure than total metal concentration in the soil.